Coping Strategies Of Students Continuing Study While Working: A Qualitative Study From A Human Resource Management Perspective - Anitiyo Soelistiyono; Juhanes Juhanes; Muryanto Agus Nuswantoro; Emy Susiatin (Community Engagement and Emergence Journal (CEEJ), 2026)
The increasing number of students continuing their studies while working is an increasingly common phenomenon in higher education. The dual role of student and employee creates various academic and work demands that can potentially lead to stress. From a human resource management perspective, this condition relates to an individual's ability to manage personal resources, balance role demands, and maintain academic and professional performance. This study aims to explore in-depth the coping strategies used by students who continue their studies while working to deal with the pressures of this dual role.This study used a qualitative approach with a phenomenological design. The research subjects consisted of three key informants, three primary informants, and three supporting informants selected through purposive sampling, with the criteria being active students who had been working for at least six months. Data were collected through in-depth interviews, observation, and documentation, then analyzed using an interactive model that encompasses data reduction, data presentation, and drawing conclusions. Based on the study's results, students who work while studying are able to manage the demands of their dual roles through adaptive coping strategies, particularly problem-focused coping, which involves time management, prioritization, and effective communication, as well as emotion-focused coping, which manages psychological stress. From a Human Resource Management perspective, these experiences contribute to human capital development by enhancing competencies such as discipline, responsibility, adaptability, communication, and problem-solving. Social support from various parties also contributes to students' success in maintaining a balance between education and work.